Inequality in Brazilian basketball: the birthplace effect - Larissa Oliveira Faria; Sarah da Glória Teles Bredt; Amanda Isadora Ribeiro; Larissa Rafaela Galatti; Maicon Rodrigues Albuquerque (Universidade Federal de Santa Catarina, 2021)
This study aimed to investigate the birthplace effect in Brazilian basketball athletes of both sexes according their states and geographical regions. Our hypothesis is that the São Paulo (SP) state is the leading player in the Southeastern region and stands out from the other regions. The birthplace of Brazilian athletes participating in the FIBA World Cup and in two national leagues were collected from open-access websites. Three hundred and fifteen athletes' birthplaces were included. The absolute and relative frequencies of athletes' birthplaces per state and geographical region were calculated. Chi-Square tests were used to compare the expected and the observed frequencies of birthplaces among regions and states. Odds Ratios and 95% confidence intervals were calculated to indicate the probability of a high-level athlete to be born in a certain region or state. The results completely confirmed our hypothesis, showing higher frequencies of athletes born in the Southeastern region, especially in the SP state. We concluded that the uneven participation in basketball in Brazil is caused by the continental dimensions of the country and the modality historical context. Concentrating basketball clubs on a single region or state (SP) leads to an underuse of the sporting potential in the country.